Positioning Halal Branding in International Trade - Nikmatul Masruroh (East Java Economic Journal, 2025)
This study aims, first, to explore the implementation of halal branding in international company, and second, to analyze the positioning of international companies utilizing halal branding. These objectives are investigated through a qualitative approach using a case study method. The study focuses on the international company PT Mitratani Dua Tujuh. The company specializes in edamame products exported to Japan, Dubai, the UK, and various other countries worldwide. Data were collected through interviews, observations, and documentation. The data were analyzed using interpretive analysis with the flow model stages of Miles and Huberman. Data validity was tested through source triangulation and technique triangulation. This research produced the following findings: first, international companies, despite holding various trade certifications such as HACCP and BRGC, must still possess halal certification. Second, international companies using halal branding can outperform competitors due to advantages in safety and health aspects. Halal branding serves as a differentiation, creating a safety barrier to entry. This study concludes that halal branding elevates products to become prestigious and differentiated offerings.